Epigenetic dysregulation of enhancers in neurons is associated with Alzheimer’s disease pathology and cognitive symptoms - Li, Peipei; Marshall, Lee; Oh, Gabriel; Jakubowski, Jennifer L.; Groot, Daniel; He, Yu; Wang, Ting; Petronis, Arturas; Labrie, Viviane (Nature communications, 2019)
Epigenetic control of enhancers alters neuronal functions and may be involved in Alzheimer’s disease (AD). Here, we identify enhancers in neurons contributing to AD by comprehensive fine-mapping of DNA methylation at enhancers, genome-wide. We examine 1.2 million CpG and CpH sites in enhancers in prefrontal cortex neurons of individuals with no/mild, moderate, and severe AD pathology ( n = 101). We identify 1224 differentially methylated enhancer regions; most of which are hypomethylated at CpH sites in AD neurons. CpH methylation losses occur in normal aging neurons, but are accelerated in AD. Integration of epigenetic and transcriptomic data demonstrates a pro-apoptotic reactivation of the cell cycle in post-mitotic AD neurons. Furthermore, AD neurons have a large cluster of significantly hypomethylated enhancers in the DSCAML1 gene that targets BACE1 . Hypomethylation of these enhancers in AD is associated with an upregulation of BACE1 transcripts and an increase in amyloid plaques, neurofibrillary tangles, and cognitive decline. Epigenetic control of enhancers may contribute to neurological disease. Here the authors carry out genome-wide analysis of DNA methylation in neurons isolated postmortem from patients with Alzheimer’s disease.